An Overview on the Socio Economic Condition of Indian Culture in Haryana: Exploring the Transition from the Ancient to Medieval Period in Indian History (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In spite of the fact that wide divisions are not hard to make, genuine issues rise when one looks for sharp isolating lines. History is a constant procedure and, in this manner, it can’t be isolated into water-tight compartments. Some random propensity or establishment has a long history before it at last develops into an unmistakable structure, and in like manner it keeps on living in some structure considerably after it appears to have stopped to exist. Along these lines in periodization one can for the most part have just harsh estimation and ought not hope to discover fixed dates. At the point when, why and how the old period closes and the medieval period starts in Indian history is extremely hard to state.